Acute Inflammatory, Cortisol, and Soreness Responses to Supramaximal Accentuated Eccentric Loading. (February 2021) - Merrigan, Justin J.; Jones, Margaret T.
Abstract : Abstract: Merrigan, JJ and Jones, MT. Acute inflammatory, cortisol, and soreness responses to supramaximal accentuated eccentric loading. J Strength Cond Res 35(2S): S107–S113, 2021—The purpose was to determine differences in time under tension, cortisol, inflammation, and perceived soreness between accentuated eccentric (AEL) and traditional loading (TRA) resistance exercise protocols. Resistance-trained men ( n = 21) completed the AEL and TRA protocols in a random order, separated by 48 hours (sets × reps at eccentric/concentric) as follows: AEL65, 3 × 5 at 120/65% 1 repetition maximum (RM); AEL80, 3 × 3 at 120/80% 1RM; TRA65, 3 × 5 at 65/65% 1RM; and TRA80, 3 × 3 at 80/80% 1RM. Four linear position transducers measured eccentric time under tension (ETUT) and total time under tension (TTUT). Ultrasonography measured vastus lateralis muscle thickness and echo intensity at baseline and immediately post-exercise. Salivary cortisol was assessed at baseline, 0-, 15-, 30-, and 60-minute post-exercise. Perceived soreness was assessed at baseline, 24-, and 48-hours post-exercise. During rep 1, AEL65 and AEL80 had longer ETUT and TTUT than TRA65 ( p ⩽ 0.002) and TRA80 ( p ⩽ 0.008), respectively. However, AEL65 had shorter ETUT (reps 3–5) and TTUT (reps 3–5) than TRA65 ( p ⩽ 0.043). Similarly, ETUT (reps 2–3) and TTUT (rep 3) was shorter in AEL80 than TRA80 ( p ⩽ 0.045). However, there was no protocol effect for ETUT and TTUT ( p > 0.05). Muscle thickness changes were trivial after each protocol (AEL80, d = 0.19; TRA80, d = 0.15; AEL65, d = 0.24; TRA65, d = 0.23), but changes in echo intensity were moderate (AEL80, d = 0.61; TRA80, d = 0.61; AEL65, d = 0.61; TRA65, d = 0.76). Salivary cortisol decreased below baseline at 30- and 60-minute post-exercise ( p ⩽ 0.006). Perceived soreness elevated from baseline to 24 hours for AEL80 ( p = 0.006). The inflammatory, cortisol, and soreness responses after AEL were either low or similar to TRA, indicating similar recovery patterns between protocols.